Hand hygiene - requirements for medical professionals - Wałaszek, Marta (Nursing Problems / Problemy Pielęgniarstwa, 2018)
Hand hygiene is the most important element in the prevention of hospital-acquired infections. Medical staff implements hand hygiene in practice through; using a 6-stage hand hygiene technique, 5-hand hygiene moments, using protective gloves, avoiding carrying anything under the elbow, wearing short natural nails. The literature related to hand hygiene has been reviewed. It was pointed out that the prob-lems we face in the implementation of hand hygiene recommendations are not only the domain of Polish medical personnel. The theory on the issue of nail painting among medical personnel was presented and sociological aspects of some conditions of hand hygiene were outlined. The aim of the work was to provide medical workers with a review of the hand hygiene literature along with their interpretation to raise awareness and emphasize the need to consistently comply with the principles of hand hygiene in the medical area.